2018
DOI: 10.7717/peerj.5433
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of metastasis-related genes reveals a gene signature predicting the survival of colon cancer patients

Abstract: ObjectiveThe mechanism underlying colon cancer metastasis remain unclear. This study aimed to elucidate the genes alteration during the metastasis of colon cancer and identify genes that crucial to the metastasis and survival of colon cancer patients.MethodsThe dataset of primary and metastasis tissue of colon cancer, and dataset of high and low metastasis capability of colon cancer cells were selected as training cohort, and the overlapped differentially expressed genes (DEGs) were screened from the training … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 37 publications
1
17
0
Order By: Relevance
“…NEDD9 coordinates the focal adhesion kinase and SRC signaling cascades that are involved in integrin-dependent adhesion and migration, invasion, cell apoptosis and life cycle, and survival 26. NEDD9 overexpression contributes to solid cancer metastasis in lung, liver, breast, ovarian, colon, glioblastoma carcinoma, and cervical cancers 3,713. NEDD9 expression levels are a biomarker of cancer aggression and could be a prognostic factor of solid cancers 14.…”
Section: Introductionmentioning
confidence: 99%
“…NEDD9 coordinates the focal adhesion kinase and SRC signaling cascades that are involved in integrin-dependent adhesion and migration, invasion, cell apoptosis and life cycle, and survival 26. NEDD9 overexpression contributes to solid cancer metastasis in lung, liver, breast, ovarian, colon, glioblastoma carcinoma, and cervical cancers 3,713. NEDD9 expression levels are a biomarker of cancer aggression and could be a prognostic factor of solid cancers 14.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, IL-8 was also found to play a central role in CRC metastasis by inducing the EMT or resistance to anoikis. A protein-protein network analysis demonstrated that IL-8 was one of the four hub genes associated with CRC metastasis [96]. Further investigations showed that IL-8 was significantly higher in patients with stage T3 or T4 CRC, lymph node metastasis or liver metastasis.…”
Section: Il-8mentioning
confidence: 96%
“…C-index, also known as concordance" statistic or C-statistic, is a measure of goodness of fit for survival outcomes in a CPH model, and higher C-index means higher predictive ability [21]. Therefore, to further confirm the performance of our multigene panel, we compared the C-indexes, calculated by using the R package "survcomp [22]" , with a total of 10 biomarkers reported by others [23][24][25][26][27][28][29][30][31][32][33]. Student T test was used to compare C-indexes between two groups.…”
Section: Comparison Of the Prognostication Performance Of Our Multigementioning
confidence: 99%
“…As mentioned above, we compared the performance of our multigene panel with 10 existing biomarkers (including a 4-gene signature [23], a 15-gene signature [24], two 6-gene signatures [25,28], a 10-gene signature [26], a 5-gene signature [27], AEBP1 [29], FZD7 [30], CDX2 [31], MUC2 [31], PPM1H [32], and LAYN [33]). As shown in figure 6, the C-index of our multigene panel was significantly higher or comparable with the existing biomarkers in the training set, test set, TCGA-COAD, and GSE17536, indicating that our multigene panel had comparable prognostication performance.…”
Section: The Prognostic Performance Of Our Multigene Panel Was Comparmentioning
confidence: 99%